Integrated induced-coherence spectroscopy in a single nonlinear waveguide - Kumar, Pawan; Saravi, Sina; Pertsch, Thomas; Setzpfandt, Frank (Physical Review A, 2020)
We present a generalized understanding of the induced-coherence (IC) effect, aiming to find new strategies for engineering and optimizing the IC response of nonlinear systems. We establish that sensing the cross density of states (CDOS) of the field lies at the core of IC and that it is the spatial profile of the nonlinearity that determines how this CDOS information is sampled. Based on our findings, we identify integrated nonlinear waveguides as a versatile and suitable platform for spectroscopy based on IC and show that our generalized treatment allows us to optimize the sensing performance. Our results open the way for the design of compact IC-based spectroscopic devices with customized responses.
CRIS-Team Scopus Importer:2023-04-20